Out-of-school-time STEM programs for females. volume II, implications for research and practice - Wiest, Lynda R.; Crawford-Ferre, Heather Glynn; Sanchez, Jafeth E. (Out-of-school-time STEM programs for females, 2020)
Vol. II: Short-Term Programs features eight OST STEM programs for females from across the United States that run one to three days in length, in most cases, a single day. In this book, the chapter authors describe their programs, the effectiveness of those programs, and practical implications of their program evaluation data. This book series is the first of its kind to offer researchers, educators, school administrators, policy makers, and others detailed insight into the promise and practice of out-of-school-time STEM programs for females.Science, technology, engineering, and mathematics (STEM) disciplines play a pivotal role in societal progress and economic prosperity, in addition to enhancing individual lives. However, U.S. students lack strong STEM performance in an international context. The pool of STEM-proficient workers is thus insufficient to fuel the nation, with females being one group that is noticeably absent.Out-of-school-time (OST) programs, which are on the rise, are increasingly suggested as a way to support and encourage underrepresented groups in STEM. Participants in OST programs have shown improved achievement, interest, and confidence in STEM, as well as greater awareness of STEM role models and careers.